PENILAIAN POTENSI WISATA BUKIT BIRAH DI KECAMATAN PANYIPATAN KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Roy Sandi Hasugian; Khairun Nisa; Fonny Rianawati (Jurnal Sylva Scienteae, 2020)
Bukit Birah is a hill that gives a view of the Kandangan Lama Village, the scenery of the sunrise and sunset, the beauty of the hills, the beach and the ocean and also the diversity of flora and fauna along the climbing path to the hills. The research was carried out to: find out the potential of the tourism landscape and assess the potential tourism of Bukit Birah. Data retrieval is done by the observation, interview and documentation, while data processing used scoring methods and itis described descriptively. The results show that the potential of Bukit Birah tourism landscape is 22, class A (high quality) so that it has the potential to be developed as a natural tourism object. The potential of tourism based on scoring is included in the medium potential with a value of 43 so it needs more development especially in terms of tourist facilities.Keywords: Potential Tourism, Bukit Birah, Tanah Laut Regency